Treatment Outcome of Supervised Exercise and Home Exercise in Patients with Symptomatic Disc Displacement: A Randomized Clinical Trial - Younas, Ayesha; Ishaq, Muhammad; Naweed, Sameen; Aamir , Maham (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the treatment outcomes of supervised and home exercises in terms of reduction in disc displacement symptoms of patients.Study Design: Randomized clinical trial. (No. NCT06651814).Place and Duration of Study:  Oral and Maxillofacial Surgery Department, Armed Forces Institute of Dentistry (AFID), Rawalpindi Pakistan, from Aug 2024 to Feb 2025.Methodology: Patients had to rate the severity of their Temporomandibular joint (TMJ) clicking sounds as ≥4 on a Numerical Rating Scale (NRS 0-10) and experience the clicking at least once a week. Follow-up evaluations were conducted 3 months after treatment. A blinded clinical examination was performed by the same examiner as at baseline, and data were collected using a predesigned questionnaire. TMJ clicking sounds were assessed using a 5-point scale, ranging from "never" to "daily."Results: The mean age was 39.24±6.26 years in Home Exercise group (Group-A) and 41.32±4.43 years in Supervised Exercise group (Group-B). Males comprised 67.0% of Group-A and 59.0% of Group-B, while females accounted for 33.0% and 41.0%, respectively (p=0.241). In Group-A, 37.0% chewed on both sides, 43.0% on the right, and 20.0% on the left, compared to 25.0%, 49.0%, and 26.0% in Group-B (χ2=3.94, p=0.174). Headaches were reported in 60.0% of Group-A and 74.0% of Group-B (χ2=4.43, p=0.035). Stiffness was noted in 63.0% of Group-A and 54.0% of Group-B (χ2=1.66, p=0.196). Parafunctional habits were present in 77.0% of Group-A and 85.0% of Group-B (χ2=2.07, p=0.149).Conclusion: Both groups developed better coping strategies and eased discomfort, but supervised jaw exercises further reduce ...